Pandangan Ulama Empat Mazhab dalam Memutuskan Upah Amil Zakat Guna Meningkatkan Optimalisasi Keprofesionalan Amil Zakat - Siti Kalimah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
Zakat is one of the pillars of Islam that is compulsory for every Muslim who is able, and his position is very important in Islam. In the management of zakat, it needs an 'amil zakat who has qualified by the provisions of Sharia. It is intended for the management of Zakat can be done optimally and professionally by Amil Zakat, so that zakat can be managed and distributed evenly to the people who are entitled to receive. With the high level of professionalism Amil Zakat, the higher the welfare of the Mustahik especially the Amil zakat. Wages or salaries are given in compensation for their work in managing Zakat to influence the effect of either directly or indirectly on the profession of managing Zakat property. The scholars argue in deciding the wages of zakat given to the Amil Zakat. The concept of Fiqh Zakat argues that the wages received by the Amil Zakat amounted to 12.5% or 1/8 from the Zakat property that has been accumulated.